Local Government Policies in Determination Development Impact Area Spatial Plan New Country Capital - Murjani Murjani; Suwardi Sagama; Muhammad Saparuddin (Jurnal Hukum Volkgeist, 2022)
The state capital will be moved from Jakarta to East Kalimantan. The buffer zone for the new State Capital must prepare early for the presence of the State Capital. There will be a new development, population migration, job competition, transport overcrowding, and air pollution. Therefore, it is necessary to know the legal policies issued by the buffer zone of the new State Capital in determining the Regional Spatial Plan (RTRW) and the factors that influence it. Normative legal research method by using a positive legal system to get a juridical answer. As a result, the buffer zone of the state capital has not issued a legal policy on the RTRW in dealing with the new state capital. There are other policies issued, for example, the North Penajam Paser Regency issued regent regulation number 22 of 2019 concerning Supervision and Control of Land Sale/purchase Transactions/Transfer of Land Rights. The issuance of the RTRW legal policy can become the legality of development carried out by local governments and the prevention of legal actions, both violations, and crimes.